ANALISIS IMPLEMENTASI ANGGARAN KAS SEBAGAI ALAT KONTROL KEUANGAN PADA CV. GARUDA PERKASA HONDA MOTOR SIBOLGA - Elisabet Vivi Sari Waruwu; Sahat Simatupang; Sriayu Aritha Panggabean (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
Implementation of the Cash Budget is a tool that is used as a tool that controls finances by using quantitative research. This study aims to determine the application of the implementation of the cash budget to financial control such as calculating the amount of cash receipts and cash disbursements for five years, namely in the 2017-2021 period, calculating budget differences (Favourable and Unfavourable Variances) and finding causes that can be controlled (Controllable) and uncontrollable or one variance. The main factor that causes the difference or difference (variance) between the budget and the realization of the cash budget is the difference in the realization of last year or the previous year. This research was conducted to find deviations that might occur so that anticipatory and revision actions can be taken immediately by using secondary data and obtained from the financial reports of CV. Garuda Mighty Honda Motor Sibolga 2017-2021. The testing technique used in this study is financial ratio analysis. The results show that jointly calculating the amount of cash receipts and cash disbursements for five years, namely in the 2017-2021 period, calculates budget differences (Favourable and Unfavourable Variances) and finds controllable and uncontrollable causes ( Uncontrollable) or one variant of the calculation, it can be seen that the implementation of the cash budget has been going well which can be seen from efforts to control all activities carried out by the company so that what has been targeted can be achieved.